RESTITUTION RIGHTS AS A CONSTRUCTION OF JUSTICE REFERRING TO THE LAW ON PROTECTION OF WITNESSES AND VICTIMS - Bambang Tri Bawono (UNISSULA, 2021)
This study aims to determine the effectiveness of restitution rights regulations for witnesses and victims based on Law No. 31 of 2014 concerning Amendments to Law No. 13 of 2006 concerning Protection of Witnesses and Victims. The provision of restitution which is the right of victims is often neglected, so that victims in their capacity as the aggrieved party do not get the rights that should be as stipulated in legislation. Based on this, this research emphasizes more on the factors that cause the ineffectiveness of regulations regarding restitution rights, as well as how efforts should be made so that victims can get restitution rights in accordance with the value of justice. The research method used in this research isresearch method library with a normative juridical approach that emphasizes secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the research state that the factors that cause the ineffectiveness of restitution rights are the victim's ignorance of the existence of the right to retribution and the procedure for filing it, the perpetrators of criminal acts are generally incapacitated, and there is no good faith for the perpetrators of crimes who generally have adequate financial capacity. Efforts that must be made so that victims get the right to restitution is to replace the application of the service model for victims of criminal acts that should position the victim as a subject who needs extra services, as stated in Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons. In addition, the current effort is to make the replacement of the right to restitution as an additional punishment which automatically becomes part of the judge's decision to be implemented immediately.